Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

A while ago I was wondering if there is a "natural" way to make a commutative group out of an arbitrary one. I played with the idea a bit and here is what I came up with.

Define a binary relation $\sim$ on a group $G$ such that $x \sim y$ if $\exists a, b \in G$ such that $ab=x$ and $ba=y$.

It's fairly easy to show this is an equivalence relation:

  • Reflexivity: $xe = ex = x$, so $x\sim x$.
  • Symmetry: obvious.
  • Transitivity: Suppose $x \sim y$ and $y \sim z$. Then $\exists a,b,c,d$ such that $ab=x$, $ba=cd=y$, and $dc=z$. Let $e = ad^{-1}$ and $f=db$. Then $ef = ad^{-1}db = ab = x$, and $fe = dbad^{-1} = dyd^{-1} = dcdd^{-1} = dc = z$. So $x \sim z$. $\square$

Question: Let $[x]$ denote the equivalence class of $G/\mathord\sim$ containing $x$. Suppose we let $[x][y] = [xy]$. Is this operation well-defined?

If so, then $G/\mathord\sim$ is clearly a group under this operation. Furthermore, it is commutative, since $[x][y] = [xy] = [yx] = [y][x]$ (where the middle equality is by definition of $\sim$).

share|cite|improve this question
A natural way to make commutative groups out of arbitrary groups is with the commutator subgroup (abelianization). See here. – Mikko Korhonen Apr 23 '14 at 6:52
up vote 3 down vote accepted

No, it is not (except in trivial cases). Note that the only element equivalent to $e$ is $e$ itself.
So if $y \in [x]$ but $y \ne x$, $y x^{-1} \in [x] [x^{-1}]$ but is not in $[x x^{-1}] = \{e\}$.

share|cite|improve this answer
Oh, shoot. In fact, these "trivial cases" are precisely those where $G$ is already commutative and $\sim$ is the equality relation. – augurar Apr 23 '14 at 6:41

Note that the equivalence relation is identical to conjugacy classes. If

$$\exists a: axa^{-1}=y$$ then $$a^{-1}axa^{-1}a=x,\;(a)(a^{-1}axa^{-1})=axa^{-1}=y$$ or on a better day just $$a^{-1}(ax)=x,\;(ax)a^{-1}=y$$ and conversely $$\exists a,b: ab=x,\;ba=y\implies aya^{-1}=x$$

share|cite|improve this answer
Interesting. You can simplify the first part by using $(xa^{-1})(a)=x$, $(a)(xa^{-1})=y$. – augurar Apr 23 '14 at 6:48
@augurar Haha that's great... this is what abstract algebra does to my brain... – NotNotLogical Apr 23 '14 at 6:49

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.